Immune checkpoint inhibitors for progressive multifocal leukoencephalopathy: Identifying relevant outcome factors. (26th July 2021) - Lambert, Nicolas; El Moussaoui, Majdouline; Maquet, Pierre
Abstract: Introduction: Progressive multifocal leukoencephalopathy (PML) is an infectious brain disease caused by JC virus in immunocompromised individuals. Immune checkpoint inhibitors (ICIs) recently emerged as a therapeutic hope for these patients but identification of those likely to respond to the treatment is still an unmet need. Method: We performed a systematic PubMed search for reports of patients treated for PML using an ICI. Clinical, biological and radiological characteristics were contrasted between patients who responded to the treatment (RP) and those who did not (NRP). Results: Thirty‐five patients were included in the present study. Twenty‐one of them reportedly benefited from the treatment. Age, blood CD4+ cells count, pretreatment viral load in the cerebrospinal fluid (CSF), PML lesions localization, treatment delay since first PML symptoms, type of ICI used and immune‐related adverse events (irAEs) occurrence did not significantly differ between RP and NRP. By contrast, a history of therapeutic immune suppression and the use of an immunosuppressive therapy at treatment initiation were significantly associated with a poor response. Besides, reaching an undetectable viral load in the CSF and reduction of the lesion load on magnetic resonance imaging after ICI administration was associated with a good clinical response. Conclusion: Current data suggest that patients with PML under immunosuppressive therapy are less likely to respond to ICIs and raises the issue of the optimal management of irAEs during ICI treatment in this setting. Abstract : We collected the characteristics of patients with progressive multifocal leukoencephalopathy (PML) treated using immune checkpoint inhibitors reported in the literature and compared those characteristics between patients who responded to the treatment and patients who did not. We found that iatrogenic immune suppression in the medical history or at treatment initiation was associated with a poor response while reaching an undetectable viral load in the cerebrospinal fluid (CSF) and reduction of the lesion load on magnetic resonance imaging (MRI) after treatment was associated with a good clinical response.